Heavy metal uptake by two radish varieties - Máthé-Gáspár, Gabriella; Anton, Attila (Acta Biologica Szegediensis, 2002)
The aim of the present study was to determine the soil effect on the toxic metal uptake of two radish (Raphanus sativus L.) varieties. In our pot study the control soil was chernozem brown forestry soil and the contaminated soil was one soil sample from a mine dump with high As, Cd, Cu, Pb, Zn content. Characters of the examined varieties differed strongly: growing rate, capacity of metal accumulation, sensitivity to heavy metal pollution. Variety with greater growing rate in juvenile stage had a smaller heavy metal uptake capacity and higher sensitivity to toxic heavy metal content, but had a higher heavy metal uptake in the control soil. Hard available and slowly translocating element (As, Pb, Co and Cu) contents of shoots were different among the two cultivars, while the easily moving metal (Cd, Zn) content was not different.